2003
DOI: 10.1038/sj.onc.1206130
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of heregulin expression inhibits tumorigenicity and metastasis of breast cancer

Abstract: The growth factor heregulin (HRG), expressed in about 30% of breast cancer tumors, activates the erbB-2 receptor via induction of heterodimeric complexes of erbB-2 with erbB-3 or erbB-4. HRG induces tumorigenicity and metastasis of breast cancer cells. Our investigation into whether HRG is a factor likely to promote tumor formation independently of erbB-2 overexpression concludes that blockage of HRG expression suppresses the aggressive phenotype of MDA-MB-231 breast cancer cells by inhibiting cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 24 publications
3
119
0
2
Order By: Relevance
“…In order to address if HRG is regulating, at least in part, a v b 3 expression through CYR61 in MDA-MB-231 cells, we have first Discussion a v b 3 integrin overexpression in tumor cells is associated with malignant progression in breast and ovarian carcinomas as well as in glioma and melanomas (Rolli et al, 2003). In the present work, we demonstrate that HRG regulates, at least in part, the expression and the functions of the integrin receptor a v b 3 in two aggressive breast cancer cellular models (MDA-MB-231 and (Tsai et al, 2003). The levels of a v b 3 integrin in MDA-MB-231 and Hs578T cells expressing the antisense HRG cDNA were downregulated when compared to their parental counterparts.…”
Section: Hrg Regulates a V B 3 Expression In Breast Cancer Cellsmentioning
confidence: 61%
See 2 more Smart Citations
“…In order to address if HRG is regulating, at least in part, a v b 3 expression through CYR61 in MDA-MB-231 cells, we have first Discussion a v b 3 integrin overexpression in tumor cells is associated with malignant progression in breast and ovarian carcinomas as well as in glioma and melanomas (Rolli et al, 2003). In the present work, we demonstrate that HRG regulates, at least in part, the expression and the functions of the integrin receptor a v b 3 in two aggressive breast cancer cellular models (MDA-MB-231 and (Tsai et al, 2003). The levels of a v b 3 integrin in MDA-MB-231 and Hs578T cells expressing the antisense HRG cDNA were downregulated when compared to their parental counterparts.…”
Section: Hrg Regulates a V B 3 Expression In Breast Cancer Cellsmentioning
confidence: 61%
“…Moreover, we have later shown that blockade of HRG in MDA-MB-231 cells inhibited cell proliferation, abolished anchorage-independent cell growth and suppressed the invasive potential of cells in vitro. In vivo, inhibition of HRG expression reduced tumor formation, size and metastatic ability of MDA-MB-231 cells (Tsai et al, 2003). Interestingly, MCF-7 cells genetically engineered to express HRG show an increase in a v b 3 levels (Tsai et al, 2000).…”
Section: Hrg Regulates a V B 3 Expression In Breast Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nature of the signal generated by ErbB receptor complexes is not only dependent upon the repertoire of ErbB receptors expressed by tumors but also the ErbB receptor ligands expressed in the tumor microenvironment. HRG, an ErbB3/ErbB4 ligand, is expressed in the microenvironment of many tumors, notably breast cancer (Tsai et al, 2003). Our data suggest that HRG, but not EGF, activates p95 ErbB2 -ErbB3 heterodimers, which has downstream effects on AKT activation and clinical implications related to disease progression and resistance to therapy.…”
Section: Discussionmentioning
confidence: 75%
“…87 Later approaches employed monoclonal antibodies to NRG. Some of the mAbs show synergy with chemotherapy on lung cancer cells.…”
Section: Her3 Strategies Involving Ligand Targetingmentioning
confidence: 99%